The high energy X-ray probe (HEX-P): science overview - García, Javier A.; Stern, Daniel; Madsen, Kristin; Smith, Miles; Grefenstette, Brian; Ajello, Marco; Alford, Jason; Annuar, Adlyka; Bachetti, Matteo; Baloković, Mislav; Beckmann, Ricarda S.; Bianchi, Stefano; et al. (Frontiers in Astronomy and Space Sciences, 2024)
To answer NASA’s call for a sensitive X-ray observatory in the 2030s, we present the High Energy X-ray Probe (HEX-P) mission concept. HEX-P is designed to provide the required capabilities to explore current scientific questions and make new discoveries with a broadband X-ray observatory that simultaneously measures sources from 0.2 to 80 keV. HEX-P’s main scientific goals include: 1) understand the growth of supermassive black holes and how they drive galaxy evolution; 2) explore the lower mass populations of white dwarfs, neutron stars, and stellar-mass black holes in the nearby universe; 3) explain the physics of the mysterious corona, the luminous plasma close to the central engine of accreting compact objects that dominates cosmic X-ray emission; and 4) find the sources of the highest energy particles in the Galaxy. These goals motivate a sensitive, broadband X-ray observatory with imaging, spectroscopic, and timing capabilities, ensuring a versatile platform to serve a broad General Observer (GO) and Guest Investigator (GI) community. In this paper, we present an overview of these mission goals, which have been extensively discussed in a collection of more than a dozen papers that are part of this Research Topic volume. The proposed investigations will address key questions in all three science themes highlighted by Astro2020, including their associated priority areas. HEX-P will extend the capabilities of the most sensitive low- and high-energy X-ray satellites currently in orbit and will complement existing and planned high-energy, time-domain, and multi-messenger facilities in the next decade.